THE IMPACT OF THE FUTURE APPLICATION OF INTERNATIONAL ACCOUNTING STANDARDS IN THE PUBLIC SECTOR IN DEVELOPING THE PERFORMANCE OF GOVERNMENT INSTITUTIONS APPLYING THE GOVERNMENT ACCOUNTING SYSTEM AND ITS CONTRIBUTION TO ACTIVATING THE ROLE BY THE FEDERAL BOARD OF SUPREME AUDIT IN THE REPUBLIC OF IRAQ - Amer Rahima Mahmoud AL-Quraishi; Prof. Dr. Emna Boumediene (American Journals, 2023)
The government accounting system is a tool used by the state through its units to implement its strategic objectives, to raise the level of services, and to provide government financial data in a clear and transparent manner on the financial situation of the state. In order to develop that system, the International Federation of Accountants sought to create a unified global framework for accounting in the public sector by adopting International Public Sector Accounting Standards (IPSAS), and one of the objectives of these standards is to convert the basis of accounting measurement from the cash basis to the accrual basis, which has an impact on the quality of financial reporting, achieves transparency, accountability, evaluates performance, and facilitates the process of integration with the international community, as well as activating the role of oversight bodies in auditing and control. As the research problem was confined to how the impact of these standards on government units and its reflection on improving the quality of the lists and financial statements and its impact on activating the role of the oversight authorities on these units, the research was built on major hypotheses that meet at the same time to implement the standards (IPSAS) that improve the quality of the accounting system A model was prepared for the financial statements of the research sample according to (IPSAS) with proving the hypotheses of the study on conducting the descriptive statistical analysis of the questionnaire prepared for that, with a statement of the results of the tests by calculating relative importance indicators, arithmetic averages, standard deviations, correlation coefficient (Pearson) and simple linear regression coefficients.The researcher concluded that there are shortcomings in the presentation and disclosure of the financial data of the study sample of the current government accounting system, and the study recommended the need to move towards the use of the experience of countries in adopting and applying standards (IPSAS) for the purpose of convergence between the systems of the world and the government accounting system approved in Iraq.
Keywords: International Public Sector Accounting Standard, Government accounting system, Non-profit Government departments, Financial statements, Iraqi public sector.